IHL and the challenges of civilian involvement in armed conflict: examining the crux of the notion of direct participation in hostilities - Lawan Haruna, Abdulrashid; Eishan Jan, Mohammad Naqib (Zesdyzar Rokman Resources, 2014)
International humanitarian law (IHL) is the branch of public international law responsible for the regulation of conduct of belligerents and it seeks to protect individuals who are not taking an active part in hostilities from the effects of armed conflict. This segment of the law has been facing serious challenges in contemporary armed conflicts due to the continuous involvement of civilians in activities that are of military nature. This paper seeks to explore the notion of direct participation in hostilities with a view to giving civilians the maximum protection they deserve in time of armed conflict without necessarily impairing imperative military necessity. It considers specific acts that will be termed as taking a direct part in hostilities, which will consequently deprive a civilian his immunity against direct attack. The paper will further discuss the nitty-gritty of the notion of direct participation in hostilities and the various critiques it receives from military perspectives coupled with its possible practical difficulty in terms of implementation. It also discusses the beginning and end of civilian direct participation in hostilities and the revolving door of civilian protection. The paper posits that notwithstanding the various contributions in trying to resolve the problems associated with direct participation in hostilities, the notion has remained critical and needs further clarification. The paper recommends that belligerents should respect their obligation in terms of civilian protection despite the challenges facing civilian involvement in the contemporary armed conflict.